2018
DOI: 10.1038/s41557-018-0021-z
|View full text |Cite
|
Sign up to set email alerts
|

Organic synthesis provides opportunities to transform drug discovery

Abstract: Despite decades of ground-breaking research in academia, organic synthesis is still a rate-limiting factor in drug-discovery projects. Here we present some current challenges in synthetic organic chemistry from the perspective of the pharmaceutical industry and highlight problematic steps that, if overcome, would find extensive application in the discovery of transformational medicines. Significant synthesis challenges arise from the fact that drug molecules typically contain amines and N-heterocycles, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
910
0
19

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,158 publications
(937 citation statements)
references
References 148 publications
8
910
0
19
Order By: Relevance
“…[17] As noted earlier,o ne of the most exciting opportunities regarding cyclic allene chemistry is the possibility of intercepting enantioenriched allenes for the synthesis of enantioenriched cycloadducts.I naseminal study,C hristl and coworkers generated 1-phenyl-1,2-cyclohexadiene in enantioenriched form, as judged by the formation of an enantioenriched cycloadduct, albeit in low yield, likely owing to the necessary use of organolithium reagents. [17] As noted earlier,o ne of the most exciting opportunities regarding cyclic allene chemistry is the possibility of intercepting enantioenriched allenes for the synthesis of enantioenriched cycloadducts.I naseminal study,C hristl and coworkers generated 1-phenyl-1,2-cyclohexadiene in enantioenriched form, as judged by the formation of an enantioenriched cycloadduct, albeit in low yield, likely owing to the necessary use of organolithium reagents.…”
Section: Angewandte Chemiementioning
confidence: 97%
See 1 more Smart Citation
“…[17] As noted earlier,o ne of the most exciting opportunities regarding cyclic allene chemistry is the possibility of intercepting enantioenriched allenes for the synthesis of enantioenriched cycloadducts.I naseminal study,C hristl and coworkers generated 1-phenyl-1,2-cyclohexadiene in enantioenriched form, as judged by the formation of an enantioenriched cycloadduct, albeit in low yield, likely owing to the necessary use of organolithium reagents. [17] As noted earlier,o ne of the most exciting opportunities regarding cyclic allene chemistry is the possibility of intercepting enantioenriched allenes for the synthesis of enantioenriched cycloadducts.I naseminal study,C hristl and coworkers generated 1-phenyl-1,2-cyclohexadiene in enantioenriched form, as judged by the formation of an enantioenriched cycloadduct, albeit in low yield, likely owing to the necessary use of organolithium reagents.…”
Section: Angewandte Chemiementioning
confidence: 97%
“…[16] Given the potential for heterocyclic allenes to provide af acile means to rapidly assemble stereochemically rich scaffolds, [16] we wondered whether oxacyclica llenes 6 could be employed efficiently in cycloadditions to access oxygencontaining heterocycles. [17] Oxygenated heterocycles are often seen in natural products and drugs [18][19][20][21] and are known bioisosteres for their nitrogen-and sulfur-containing counterparts. [22] Asingle report by Christl and Schreck demonstrated that 6 (R' = H) could be generated using the Doering-Moore-Skattebøl rearrangement, however, this required harsh organolithium-based conditions.…”
mentioning
confidence: 99%
“…[18,19] Inspiriert durch die große Anwendungsbreite der lichtinduzierten Rutheniumkatalyse wollten wir deren Wirkungsmechanismus aufklären (Schema 3). Dem folgend wurden wichtige funktionelle Gruppen wie Imide,E none,P iperidylringe oder Ester als Struktureinheit der Alkylbromide 2 toleriert, und die rutheniumkatalysierte lichtinduzierte meta-C-H-Funktionalisierung erfolgte weiterhin mit hoher Effizienz.…”
Section: Angewandte Chemieunclassified
“…68 Polyazines are often found in therapeutic compounds (eq 1), and they are also abundant in medicinal chemistry libraries as lead compounds and drug fragments 9. Given the importance of polyazines in pharmaceuticals, site-selective functionalization strategies would be highly desirable 10. We herein report a study that addresses this challenge by selectively installing a phosphonium ion as a generic functional handle in polyazine structures.…”
Section: Introductionmentioning
confidence: 99%